The Effect of the Problem-Based Learning Model on Student Activeness in Science Learning - Dewi Nur Irma Lailatul Safitri; Enik Setiyawati (research, training and philanthropy institution Natural Aceh, 2023)
This research aims to determine student activeness by implementing the problem-based learning model in elementary school science education. It is a quantitative research study with the entire 5B class population. The design used in this study is a one-shot case study, and data collection involved using observation sheets to measure student activeness. The subjects of this research are 31 students from class 5B at SDN Oro-Oro Ombo Wetan 1. Data collection utilized validity tests, reliability tests, tests for prerequisite analysis of normality, and the results of the T-test (One-Sample Statistics) with a significance level of 5% (0.05), yielding a significant t-value (2-tailed) of 0.004. Based on the validity results, all 30 observation items and 31 student responses were deemed valid. The reliability test indicated reliability, and the normality test confirmed that the residual values were normally distributed. The t-test result showed that the significance value of student activeness was 0.004, less than 0.05. Therefore, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. This means that there is an influence of the problem-based learning model on student activeness in science learning. If this model is implemented in elementary schools, it will positively impact student activeness and engagement in the learning process.